Onco-cardiology: Drug-drug interactions of antineoplastic and cardiovascular drugs. (January 2020) - Akbulut, Muge; Urun, Yuksel
Abstract: Cardiovascular diseases (CVD) and cancer are still the leading causes of death. There are many common etiologic factors, especially smoking and obesity. Therefore, it is not uncommon for CVD and cancer to coexist. Drug-drug interactions (DDIs) inevitably occur in this group of patients, where polypharmacy is increasing due to older age and multiple comorbidities. However, multidisciplinary studies, especially close collaboration of medical oncologists and cardiologists, who deals with the diagnosis and treatment of these diseases, awareness and preventive approaches to DDIs may reduce serious morbidity and mortality. In this review, information about the common treatments used in cardiology and oncology and possible DDIs are discussed.